The unbooked maternity patient in an academic hospital in Durban - R. Gcaba; H.B. Brookes (AOSIS, 1992)
This paper examines the unbooked maternity patient in an academic hospital in Durban, Natal; This hospital is the biggest hospital serving the underprivileged population of this area. Of the 16000 annual deliveries in this hospital, about 12% are unbooked patients. The health belief model of Rosenstock, as interpreted by Mikhail and Cox's interaction model of client health behaviour were used as a theoretical framework for this research. A qualitative case study methodology was undertaken and semi-structured interviews were conducted with unbooked mothers who had utilized appropriate health services in a previous pregnancy. The aim of such interviews was to explore reasons given by mothers for non-use of facilities in the current pregnancy. The basic trends reflected in the findings regarding non-utilization of health services were client instability, health service failure and socio-cultural constraints, The study is innovative and addresses the problem from a social-cultural and midwifery perspective.